"Ode to confidence": Poetry groups for dysarthria in multiple sclerosis. (3rd May 2020) - Balchin, Rebecca; Hersh, Deborah; Grantis, Jamaica; Godfrey, Maddie
Abstract: Purpose: Approximately 40–50% of people with multiple sclerosis (MS) have dysarthria impacting confidence in communication. This study explored how people with MS experienced a novel therapeutic approach combining dysarthria therapy with poetry in a group format. Method: Participants were recruited through MSWA (formerly known as the Multiple Sclerosis Society of Western Australia), a leading service provider for people living with all neurological conditions in Western Australia. They attended eight weekly sessions led by a speech pathologist and a professional poet. The study was co-designed and qualitative, using observational field notes recorded during sessions and semi-structured in-depth interviews with participants after programme completion. The results from an informal, unstandardised rating scale of communication confidence, along with standardised voice and speech measures, were used to facilitate discussion about confidence in the interviews. Result: Nine participants with MS completed the group programme. Analysis of the qualitative data revealed participants' positive views regarding the pairing of speech pathology and poetry. Thematic analysis identified four core themes: living with MS and its "series of griefs"; belonging to a group – "meeting with a purpose"; the power of poetry; and poetry as a medium for speech pathology. Conclusion: Poetry in combination with dysarthria therapy represents a novel, interprofessional approach for improving communication confidence in individuals with MS.